Fugu ESTs: New Resources for Transcription Analysis and Genome Annotation - Clark, Melody S.; Edwards, Yvonne J.K.; Peterson, Dan; Clifton, Sandra W.; Thompson, Amanda J.; Sasaki, Masahide; Suzuki, Yutaka; Kikuchi, Kiyoshi; Watabe, Shugo; Kawakami, Koichi; Sugano, Sumio; Elgar, Greg; et al. (Genome Research, 2003)
The draft Fugu rubripes genome was released in 2002, at which time relatively few cDNAs were available to aid in the annotation of genes. The data presented here describe the sequencing and analysis of 24,398 expressed sequence tags (ESTs) generated from 15 different adult and juvenile Fugu tissues, 74% of which matched protein database entries. Analysis of the EST data compared with the Fugu genome data predicts that approximately 10,116 gene tags have been generated, covering almost one-third of Fugu predicted genes. This represents a remarkable economy of effort. Comparison with the Washington University zebrafish EST assemblies indicates strong conservation within fish species, but significant differences remain. This potentially represents divergence of sequence in the 5′ terminal exons and UTRs between these two fish species, although clearly, complete EST data sets are not available for either species. This project provides new Fugu resources, and the analysis adds significant weight to the argument that EST programs remain an essential resource for genome exploitation and annotation. This is particularly timely with the increasing availability of draft genome sequence from different organisms and the mounting emphasis on gene function and regulation.